Sufism Psychotherapy: Hudur al-Qalb Method For Mental Health - Irham, M. Iqbal (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2023)
This study aims to explain hudur al-qalb as a tasawuf psychotherapy method for mental health. As a literature research, this article will examine hudur al-qalb in the thinking of Sufi experts, such as al-Ghazali and Ibn al-’Arabi, and to what extent it can provide benefits in mental health, namely peace of mind and soul. This research has implications for efforts to cure mental stress by tasawuf psychotherapy. This research is qualitative in nature, namely it is carried out by collecting, analyzing, and interpreting narratives comprehensively on visual data to gain complete, comprehensive and holistic insight into the phenomenon of hudur al-qalb. The results of the study found that Hudur al-qalb is a condition in which the heart is awake, namely in a stand-by position. This vigilance keeps the heart in awareness, and of course in vigilance. This wakefulness keeps the heart in awareness and in ‘mindfulness’. This condition leads to intelligence of mind, meaning of life, clarity of heart, as well as silence and reassurance of the soul. In addition, this condition can also eliminate mental anxiety and reduce negligence.